Surfactant‐mediated formation of alginate layers at the water‐air interface. (11th September 2019) - Degen, Patrick; Paulus, Michael; Zwar, Elena; Jakobi, Victoria; Dogan, Susanne; Tolan, Metin; Rehage, Heinz
Abstract : The self‐organization process of polysaccharide alginate with different cationic surfactants at the water‐air interface was investigated over a wide concentration regime. The changes of surface properties determined by surface tension measurements, surface rheology, and X‐ray reflectivity are correlated with changes of bulk properties measured by turbidity, light scattering, and zeta potential measurements. We demonstrate that the interactions between the alginate and cationic surfactants result in significant changes of bulk and interfacial properties. The results of surface shear experiments point to the existence of highly viscoelastic interfacial films. In combination with X‐ray reflectivity, we demonstrate that these rheological features are related to polymer‐surfactant associations at the interface. In the regime of high surfactant concentrations, we observed the existence of multilayer structures.